2022
DOI: 10.1371/journal.pone.0263455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined training on metabolic profile, lung function, stress and quality of life in sedentary adults: A study protocol for a randomized controlled trial

Abstract: Background Both physical inactivity and sedentary behavior are considered modifiable risk factors for chronic diseases and all-cause mortality. Adult office-workers spend most of their working day in sedentary behaviors, so they are particularly at high risk of developed chronic diseases (e.g., cardiovascular diseases, metabolic disorders like diabetes mellitus, …). It seems important to promote behavioral changes that could prevent or delay metabolic disease development. Evidence supports the use of exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
(150 reference statements)
0
3
0
2
Order By: Relevance
“…Os artigos eleitos estão descritos de forma resumida e esquemática no Quadro 3, abaixo, quanto a fonte e data, estudo, desenho experimental, intervenção e resultados. Houve predomínio de obeso do sexo masculino na grande maioria dos estudos sendo um realizou intervenções com mulheres e grande parte dos estudos tinham jovens sedentários também obesos, como amostra total (100% No tocante à porcentagem entre o grupo experimentais que participaram de intervenções de sequência com 12 semanas (Navarro-Lomas et al, 2022;Silva et al, 2022;Ezzati et al, 2021;Mombeyni et al, 2021;Amaro Gahete et al, 2021) 16 semanas (Ferreira et al, 2022), houve diferença, indicando que o TC se faz mais vantajoso para controle dessas variáveis metabólicas, tendo registrado ainda diminuição também em biomarcadores pró-inflamatórios e de estresse oxidativo também em mulheres. Sendo em Moghadam, et al (2022) um diferencial ao usar o açafrão como suplementação associada ao TC, onde está associação se mostrou bastante eficiente em potencializar a resposta anti-inflamatórios decorrentes deste tipo de exercício, podendo este tipo de intervenção com alimentos funcionais ser mais bem estudada, para a obtenção de resultados mais consistentes (Ferreira et al, 2022).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os artigos eleitos estão descritos de forma resumida e esquemática no Quadro 3, abaixo, quanto a fonte e data, estudo, desenho experimental, intervenção e resultados. Houve predomínio de obeso do sexo masculino na grande maioria dos estudos sendo um realizou intervenções com mulheres e grande parte dos estudos tinham jovens sedentários também obesos, como amostra total (100% No tocante à porcentagem entre o grupo experimentais que participaram de intervenções de sequência com 12 semanas (Navarro-Lomas et al, 2022;Silva et al, 2022;Ezzati et al, 2021;Mombeyni et al, 2021;Amaro Gahete et al, 2021) 16 semanas (Ferreira et al, 2022), houve diferença, indicando que o TC se faz mais vantajoso para controle dessas variáveis metabólicas, tendo registrado ainda diminuição também em biomarcadores pró-inflamatórios e de estresse oxidativo também em mulheres. Sendo em Moghadam, et al (2022) um diferencial ao usar o açafrão como suplementação associada ao TC, onde está associação se mostrou bastante eficiente em potencializar a resposta anti-inflamatórios decorrentes deste tipo de exercício, podendo este tipo de intervenção com alimentos funcionais ser mais bem estudada, para a obtenção de resultados mais consistentes (Ferreira et al, 2022).…”
Section: Resultsunclassified
“…Os resultados da análise do subgrupo percentual de gordura corporal mostraram que pessoas sem aptidão previa ou treinamento pregresso, homens idosos, foram mais propensos a obter a vantagem durante períodos programados de TC (Bouamra et al, 2022;Ferreira et al, 2022;Moghadam et al, 2022;Navarro-Lomas et al, 2022) e esta vantagem foi relatada logo nas primeiras semanas sendo a 12 semana de intervenção, nitidamente significativa após a 12ª semana (Singh et al, 2022;Silva et al, 2022;Ezzati et al, 2021;Mombeyni et al, 2021). Não houve diferença correlacionadas na porcentagem de cortisol nos períodos estudados, os hormônios séricos entre presentes em (Singh et al, 2022;Silva et al, 2022;Ezzati et al, 2021) Deste modo, com os dados apresentados aqui é possível elucidar muitas dúvidas sobre as respostas fisiológicas provenientes de programas variados de TC para homens obesos sedentários jovens e/ou os de meia idade e ainda os idosos.…”
Section: Resultsunclassified
“…Many Filipino PE teachers see EAP as a common and acceptable practice to discipline students, but they need to be aware of the potential drawbacks of this approach. It has been noted that many people believe that exercise can help individuals improve their physical fitness and health [10,11], develop self-control and a sense of responsibility, and manage misbehavior [9,7]. However, there is also evidence that EAP can lead to negative attitudes toward physical activity, a lack of engagement with exercise, and physical harm [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Requiring individuals to perform physical activities for their misbehavior can prompt them to follow the rules and take responsibility for their actions [9]. Additionally, exercise can promote physical fitness and health, benefiting sedentary and inactive individuals [10,11]. On the contrary, potential drawbacks to using EAP have been observed.…”
mentioning
confidence: 99%
“…Sedentary behavior and physical inactivity are now recognized as important causal factors in the development of insulin resistance (IR) and type 2 diabetes (T2DM) 1 , 4 6 . Evidence showed that even a short-term (14 days) reduction in physical activity with increased sedentary behavior leads to a reduction in multi-organ insulin sensitivity and muscle insulin sensitivity index, and concomitant increases in central and liver fat and LDL-cholesterol 5 .…”
Section: Introductionmentioning
confidence: 99%